UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MELALUI PENGGUNAAN MEDIA BAAMBOOZLE KELAS IV UPT SD NEGERI BATURETNO I TUBAN - Iis Daniati Fatimah; Novialita Angga Wiratama; Fera Dwi Darti (Jurnal Tunas Pendidikan, 2025)
Classroom action research is the research used in this study. The purpose of the research is to describe the improvement of learning outcomes in IPAS for grade IV after the use of Baamboozle game media. The data collection methods used include interIVews, observations, documentation, and tests. The research subjects consisted of 28 students, comprising 12 male students and 16 female students. Based on the research results, it was found that 14 students or 74% of all students scored below 60, compared to the first cycle data where only 10 students or 53% had scores below 60, while the number of students who were not yet finished is 5 students or 26% who scored above 70. The results of the observation of student actiIVties in learning consists of: 1) students make an effort to ask questions if there is something they do not understand; 2) students make an effort to solve IPAS problems in their own way; 3) students make an effort to complete IPAS problems following the steps that have been outlined. Keywords: Learning outcomes; IPAS; Baamboozle Media